Character Design for Sadewa Krama Cinta Sejati Webcomic - Restifar Amalia Istiqomah; Restu Ismoyo Aji; Bayu Setiawan (Texture : Art And Culture Journal, 2025)
This article discusses the design of the main characters of the webcomic Sadewa Krama: Cinta Sejati published on the LINE Webtoon Kanvas platform. This design aims to increase the awareness of individuals aged 16-24 years old towards wayang culture. Wayang is an Indonesian culture that must be preserved. However, as time goes by, the art of wayang has experienced a process of decline due to development of the era. This is due to the language element of the puppet performance which uses the Regional Language (Javanese) and the performance time is at night. Through descriptive qualitative research methods (interviews, observations, and questionnaires) to collect and analyze data as visual concepts. It was revealed that respondents from the questionnaire tended to prefer staying up late to play gadgets. The phenomenon of the development of this era requires wayang to adapt. Hence, there is a need to transfer of mediums to adapt one medium to another. In accordance with this, the right media to communicate the story is a webcomic that can also be accessed through gadgets. Not stopping there, a story that has relevance to the problems of today's teenagers is needed. Problems that they face, for example, the formation of behavior and the search for compatibility with themselves and the environment. Lakon carangan Sadewa Krama is considered to have relevance to these problems. The character design in the webcomic is realized by adapting wayang kulit characters, combined with wayang wong, then represented in a semi-realist/semi-cartoon drawing style.